A Systematic Review of Health State Utility Values in the Plastic Surgery Literature. Issue 11 (29th November 2021) - Christopher, Adrienne N.; Morris, Martin P.; Patel, Viren; Klifto, Kevin; Fischer, John P.
Abstract : Background: Cost-utility analyses assess health gains acquired by interventions by incorporating weighted health state utility values (HSUVs). HSUVs are important in plastic and reconstructive surgery (PRS) because they include qualitative metrics when comparing operative techniques or interventions. We systematically reviewed the literature to identify the extent and quality of existing original utilities research within PRS. Methods: A systematic review of articles with original PRS utility data was conducted in accordance with the Preferred Reporting Items for a Systematic Review and Meta-Analysis guidelines. Subspecialty, survey sample size, and respondent characteristics were extracted. For each HSUV, the utility measure [direct (standard gamble, time trade off, visual analog scale) and/or indirect], mean utility score, and measure of variance were recorded. Similar HSUVs were pooled into weighted averages based on sample size if they were derived from the same utility measure. Results: In total, 348 HSUVs for 194 disease states were derived from 56 studies within seven PRS subspecialties. Utility studies were most common in breast (n = 17, 30.4%) and hand/upper extremity (n = 15, 26.8%), and direct measurements were most frequent [visual analog scale (55.4%), standard gamble (46.4%), time trade off (57.1%)]. Studies surveying the general public had more respondents (n = 165, IQR 103–299) than those that surveyed patients (n = 61, IQR 48–79) or healthcare professionals (n = 42, IQR 10–109). HSUVs for 18 health states were aggregated. Conclusions: The HSUV literature within PRS is scant and heterogeneous. Researchers should become familiar with these outcomes, as integrating utility and cost data will help illustrate that the impact of certain interventions are cost-effective when we consider patient quality of life.